ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PERMINTAAN TENAGA KERJA PADA INDUSTRI KECIL KERAJINAN DI PROPINSI MALUKU - Dientje Rumerung (Soso-Q : Jurnal Manajemen, 2017)
This study aims to determine and analyze the influence of Wages, Human Capital, intensity of use of production factors, capital, goods and Request for Production of Labor requests Maluku Province.The model used is multiple linear regression models are useful for testing and estimating the effect of partial or simultaneous set of independent variables on the dependent variables. Area sampling techniques are combined with Purposive Sampling Method Sampling Method with a selected sample area to be investigated which produce the sample of 148 respondents.The findings in this study is that with variable degrees of freedom 0.10 working capital, production, and significant negative effect on employment. While the variable wage, education level and Demand of goods does not affect the demand for labor in small craft industries in the province of Maluku.This analysis is closely related to the nature of the industrial production of small craft that are orders resulted in the development of small craft industries in the province of Maluku to grow. Oroduksi nature of the orders on one side and labor utilization from dulikan family irrespective of educational level is a condition that makes small craft industries to flourish. Keywords: Growth Enterprises, Production - Workers Demand